Optical cross-connect system incorporated with newly developed operation and management system. - Shiragaki, T. (IEEE Journal on selected areas in communications)
The optical cross-connect (OXC) system described in this paper increases the operation flexibility and reliability of the trunk-line optical networks used for data communication. It features an OXC node comprised of a photonic switching network and a conventional electric switching network that are connected hierarchically. The operation and management scheme proposed for this OXC system uses the concept of an optical path and an optical section. The OXC system allows hitless network reconfiguration by switching the photonic switches gradually and without interference effects. An experimental OXC network showed that a broken optical path is restored, by rerouting, within 50 ms. Experiments using a LiNbO3 8×8 photonic switch matrix also showed that the OXC system provides photonic hitless switching. These results confirm the feasibility of flexibly reconfigurable and fast-restorable OXC systems